Shedding Light on the Role of Neurotransmitters in the Microenvironment of Pancreatic Cancer - Liang, Yiyi; Li, Huimin; Gan, Yu; Tu, Hong (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic cancer (PC) is a highly lethal malignancy with a 5-year survival rate of less than 8%. The fate of PC is determined not only by the malignant behavior of the cancer cells, but also by the surrounding tumor microenvironment (TME), consisting of various cellular (cancer cells, immune cells, stromal cells, endothelial cells, and neurons) and non-cellular (cytokines, neurotransmitters, and extracellular matrix) components. The pancreatic TME has the unique characteristic of exhibiting increased neural density and altered microenvironmental concentration of neurotransmitters. The neurotransmitters, produced by both neuron and non-neuronal cells, can directly regulate the biological behavior of PC cells via binding to their corresponding receptors on tumor cells and activating the intracellular downstream signals. On the other hand, the neurotransmitters can also communicate with other cellular components such as the immune cells in the TME to promote cancer growth. In this review, we will summarize the pleiotropic effects of neurotransmitters on the initiation and progression of PC, and particularly discuss the emerging mechanisms of how neurotransmitters influence the innate and adaptive immune responses in the TME in an autocrine or paracrine manner. A better understanding of the interplay between neurotransmitters and the immune cells in the TME might facilitate the development of new effective therapies for PC.